Tau pathology reshapes GFAP‐positive astrocytes phenotype - Zimmer, Eduardo R.; Bellaver, Bruna; Brum, Wagner Scheeren; Ferreira, Pamela C.L.; Povala, Guilherme; da Rocha, Andreia Silva; de Souza, Débora Guerini; De Bastiani, Marco Antônio (Alzheimer's & dementia, 2021)
Background Astrocytes are glial cells widely distributed in the human brain. It is well established that they perform vital functions for proper brain functioning. In pathological conditions, they adapt by changing morphology, function, and overexpressing specific proteins, such as the glial fibrillary acidic protein (GFAP). This phenomenon is called astrocyte reactivity and it is present in Alzheimer’s disease (AD). It is now a consensus that reactive astrocytes present multiple phenotypes, which are likely driven by specific pathological agents. In this context, whether tau pathology induces changes in astrocyte phenotypes is not precisely understood. Here, we aimed at evaluating hippocampal astrocyte phenotypes in the presence of tau pathology in a transgenic human tau mouse model. We hypothesize that hippocampal astrocytes will respond to tau pathology by assuming a reactive phenotype. Method Hippocampal GFAP‐positive astrocytes data from 6 month‐old PS19 mice (Prnp.Tau.P301S.tg.B6N, n = 6), which harbor the microtubule‐associated protein tau human P301S mutation, and wild‐type littermates (WT, n = 5) were obtained from GEO (GSE129797) and used to identify differentially expressed genes (DEGs) and changes in biological processes. Initially, raw fastq data reads were submitted to quality control assessments. Then, Salmon algorithm was used on high quality RNAseq samples. DEGs were evaluated using the DESeq2 method. Further data analysis included Gene Ontology (GO) functional evaluation. All analyses were performed using R/Bioconductor. Result Principal component analyses (PCA) clearly differentiated gene expression from PS19 and WT hippocampi GFAP+ astrocytes (Figure 1A). We identified 1264 up‐regulated and 634 down‐regulated genes in PS19 astrocytes in comparison to WT mice (Figure 1B‐C). Remarkably, neuronal death was the first hit among the top 10 altered GO terms (Figure 1D). Conclusion We identified a phenotypic gene expression profile in hippocampal astrocytes of mice presenting with tau pathology. Therefore, our findings suggest tau pathology changes astrocyte phenotypes, which may help in advancing our understanding of AD pathophysiology.